Anomalies in Daily Anisotropy During the Transition Period of Solar Cycles 24 and 25 - Konkathi, Manikanta; Joshi, Kaustubh Vijay (Journal of Research in Science and Engineering, 2025)
The behavior of the diurnal variability of cosmic rays during the transition period of solar cycles 24 and 25 have been investigated in the present study. Cosmic ray anisotropy exhibited a characteristic feature from 2018 to 2021 at the end of solar activity cycle 24 and the beginning of solar cycle 25; characterized by a remarkably reduced diurnal amplitude and an unconventional low - phase distribution. Observations were carried out using data from eight neutron monitors with 2.0 to 7.0 GV cut - off rigidity over a long period of five and a half solar cycles. Significant discrepancies were observed in the amplitude and phase of the first harmonic of cosmic ray variation. The GCR modulation during solar minima 24/25 differs significantly from previous solar minima in several respects, particularly in terms of the low number of sunspots, weak interplanetary magnetic fields, and turbulence. According to the analysis, this anomaly is observed throughout various rigidities and latitudes, implying a global impact.